2021
DOI: 10.1080/09553002.2021.1987571
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression for biodosimetry and effect prediction purposes: promises, pitfalls and future directions – key session ConRad 2021

Abstract: In a nuclear or radiological event, an early diagnostic or prognostic tool is needed to distinguish unexposed from low-and highly-exposed individuals with the latter requiring early and intensive medical care. Radiation-induced gene expression (GE) changes observed within hours and days after irradiation have shown potential to serve as biomarkers for either dose reconstruction (retrospective dosimetry) or the prediction of consecutively occurring acute or chronic health effects. The advantage of GE markers li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…Animal studies have indicated that the effects of irradiation are manifested in males and females differently, with females being more sensitive to radiation injury. 18 , 61 , 62 In humans, long-term radiosensitivity is higher in females even when both sexes receive a comparable radiation dose. 63 , 64 In addition, females have a significantly higher risk of dying from radiation-associated cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies have indicated that the effects of irradiation are manifested in males and females differently, with females being more sensitive to radiation injury. 18 , 61 , 62 In humans, long-term radiosensitivity is higher in females even when both sexes receive a comparable radiation dose. 63 , 64 In addition, females have a significantly higher risk of dying from radiation-associated cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 13 Several studies from various investigators have profiled transcriptomic changes in various tissues of nonhuman primates (NHPs). 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 However, the majority of these publications are with baboons, which are no longer used for such studies. Therefore, there is a need for studies performed with rhesus and cynomolgus, which are commonly used NHPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the caveat that there are species specific 36 and even strain specific differences 37 , 38 in radiation response, we trained an algorithm using the transcriptomics datasets available in the NCBI Gene Expression Omnibus database for quantitative radiation responses at 24 h. From this analysis we selected the top dose-correlated genes (positive and negative) and trained and tested our method using the net signal (N) as a correlate of dose. Typically, gene signatures that have potential for field applications are viewed to consist of a few genes to tens of genes 39 41 . Therefore, we started with 30 top ranked genes for quantitative RT-PCR testing, then further reduced the number of genes to a lower threshold, beyond which addition of more genes would not dramatically change the average error measured by RMSE.…”
Section: Discussionmentioning
confidence: 99%
“…With the caveat that there are species speci c 34 and even strain speci c differences 35,36 in radiation response, we trained an algorithm using the transcriptomics datasets available in the NCBI Gene Expression Omnibus database for quantitative radiation responses at 24 h. From this analysis we selected the top dose-correlated genes (positive and negative) and trained and tested our method using the net signal (N) as a correlate of dose. Typically, gene signatures that have potential for eld applications are viewed to consist of a few genes to tens of genes [37][38][39] . Therefore, we started with 30 top ranked genes for quantitative RT-PCR testing, then further reduced the number of genes to a lower threshold, beyond which addition of more genes would not dramatically change the average error measured by RMSE.…”
Section: Discussionmentioning
confidence: 99%